2008
DOI: 10.1177/0734242x07087661
|View full text |Cite
|
Sign up to set email alerts
|

Report: Healthcare waste characterization in Chittagong Medical College Hospital, Bangladesh

Abstract: Healthcare waste management (HCWM) options are inconsistent in Bangladesh. One of the first critical steps in the process of developing a reliable waste management plan requires a comprehensive understanding of the quantities and characteristics of the waste that needs to be managed. This study took into consideration both the quantity and quality of the generated waste to determine the generation rates and physical properties of healthcare waste (HCW) in Chittagong Medical College Hospital (CMCH) and also to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…21 Hospital should ensure the implementation of waste management plan to avoid the health and environmental hazards. 22 , 23…”
Section: Discussionmentioning
confidence: 99%
“…21 Hospital should ensure the implementation of waste management plan to avoid the health and environmental hazards. 22 , 23…”
Section: Discussionmentioning
confidence: 99%
“…Food waste from hospital food service can be divided into kitchen waste and plate waste and mostly research on food waste in hospitals are primarily based on individual plate waste mainly because of its direct influence on patient nutritional outcomes. Plate waste as in the hospital setting refers to the remaining served food which are left and not eaten by patients [ 3 4 5 6 ]. A recent review of the global hospital food waste conducted in 2018 concluded that, hospital plate waste were measured from 6% to 65%, but more commonly between 15% and 35% with a median individual plate waste of 31% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, a total of 2490 kg/day HCW (0.57 kg/patient/day, of which 0.21 kg/patient/day was HW and the rest 0.36 kg/patient/day was non-HW) was produced in Chittagong Medical College Hospital. The amount of HCW produced in the hospital was positively correlated with the number of beds ( r s = 0.79, P < 0.01) [15]. A study carried out in Iran and involved 14 hospitals indicated that the HCW generation rate was comprised of 51.6% of infectious waste, 47.2% general waste and 1.2% sharps [16].…”
Section: Introductionmentioning
confidence: 99%